Pathological impact and medical applications of electromagnetic field on melanoma: A focused review - Duan, Yunxiao; Wu, Xiaowen; Gong, Ziqi; Guo, Qian; Kong, Yan (Frontiers in Oncology, 2022)
Electromagnetic Field (EMF) influences melanoma in various ways. EMF can be classified into extremely low-frequency electromagnetic field, low-frequency magnetic field, static moderate magnetic field, strong electromagnetic field, alternating magnetic field, and magnetic nanoparticles. Each type of EMF influences melanoma development differently, and the detailed influence of each specific type of EMF on melanoma is reviewed. Furthermore, EMF influences melanoma cell polarity and hence affects drug uptake. In this review, the impacts of EMF on the effectiveness of drugs used to treat melanoma are listed according to drug types, with detailed effects according to the types of EMF and specific melanoma cell lines. EMF also impacts clinical therapies of melanoma, including localized magnetic hyperthermia, focalized thermotherapy, proton radiation treatment, nanostructure heating magnetic hyperthermia, radiation therapy, Polycaprolactone-Fe3O4 fiber mat-based bandage, and optune therapy. Above all, EMF has huge potential in melanoma treatment.